2020
DOI: 10.1021/acsanm.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanosheets Decorated with Graphite-Like Carbon Nitride Quantum Dots as Photoanodes in Photoelectrochemical Water Splitting

Abstract: The efficient utilization of solar power is becoming an important strategy for its conversion into a storable, clean, and renewable energy source like H 2 . To generate H 2 as a chemical fuel from solar power, attempts are being made to establish photoelectrochemical (PEC) water splitting as an efficient, greener pathway. Here, the surfaces of ZnO 2D nanosheets are adorned by graphite-like carbon nitride (g-C 3 N 4 ) quantum dots (QDs) with the intention of developing efficient photoanodes. Sensitization of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…ZnO was chosen as the carrier material of the nanostructure. It is widely used as a functional material in several optoelectronic applications such as light-emitting diodes (LEDs), dye PV cells, sensors, , thermoelectric devices, transistors, photoelectrodes, , and photo-assisted batteries because it presents a unique combination of functional properties, structural properties, chemical stability, and tunable micro/nanostructure. , In terms of functional properties, semiconducting ZnO has an optical gap of 3.37 eV at 300 K, a resistivity of 10 –4 Ω Cm, and an electronic mobility between 10 and 60 cm 2 s –1 V –1 depending on the microstructure . At the atomic scale, ZnO can crystallize in three different forms: cubic (rocksalt), face-centered cubic (blende), and compact hexagonal (wurtzite).…”
Section: Introductionmentioning
confidence: 99%
“…ZnO was chosen as the carrier material of the nanostructure. It is widely used as a functional material in several optoelectronic applications such as light-emitting diodes (LEDs), dye PV cells, sensors, , thermoelectric devices, transistors, photoelectrodes, , and photo-assisted batteries because it presents a unique combination of functional properties, structural properties, chemical stability, and tunable micro/nanostructure. , In terms of functional properties, semiconducting ZnO has an optical gap of 3.37 eV at 300 K, a resistivity of 10 –4 Ω Cm, and an electronic mobility between 10 and 60 cm 2 s –1 V –1 depending on the microstructure . At the atomic scale, ZnO can crystallize in three different forms: cubic (rocksalt), face-centered cubic (blende), and compact hexagonal (wurtzite).…”
Section: Introductionmentioning
confidence: 99%
“…In another work, the effect of boron addition and carbon nitride content did increase the H 2 evolution up to 85% compared to the bare TiO 2 , which is mainly due to charge carriers' generation and separation [109]. It was also shown that the photoconversion efficiency of the low charge-transfer resistance of ZnO decorated with g-C 3 N 4 is 2.3 times higher than that of pure ZnO [406]. As discussed previously, this composite had a high specific surface area, promising electronic conductivity, and excellent charge transfer interfaces and would be excellent candidates for the water splitting and H 2 evolution [407].…”
Section: Application Of Metalmentioning
confidence: 91%
“…Other metal oxide-g-C 3 N 4 based composites such as WO 3 -g-C 3 N 4 and ZnO-g-C 3 N 4 are used for H 2 generation. Mahala et al demonstrated that the prepared ZnO nanosheets decorated with g-C 3 N 4 quantum dots composites on the fluorine-doped tin oxide (FTO) coated glass slide could be utilized as a photoanode for water splitting via PEC (Figure 17b) [406]. In another work, the effect of boron addition and carbon nitride content did increase the H 2 evolution up to 85% compared to the bare TiO 2 , which is mainly due to charge carriers' generation and separation [109].…”
Section: Application Of Metalmentioning
confidence: 99%
“…It was reported that various ZnO nanostructures (such as wire, rod, belt, wafer, spheres, etc. ) can be prepared by adding surfactants or polymers in a precursor base on two different strategies: acting as templates or structure directing agents and controlled crystallization (including adjusting amount of nucleation sites, controlling growth rates, and adjusting the pH value of precursor solution). , The crystallization process of ZnO in aqueous solution is strongly reliant on the pH of the solution; in other words, the pH of the precursor solution is a key factor for modulating the ZnO surface structure . Moreover, there is modulation of the growth velocity of specific ZnO facets by passivating the other facets in consideration of its positive polar plane rich in Zn cations and negative polar plane rich in O anions. …”
Section: Optimization and Modulation Strategiesmentioning
confidence: 99%